Formação de formadores de professores de matemática: Identificação de possibilidades e limites da estratégia de organização de grupos colaborativos - Traldi Júnior, Armando (2006)
The purpose of this work is to understand the possibilities to construct a work group of the collaborative type, from a collective work group, constituted of formers of teachers who teach the discipline of Differential and Integral Calculus, in an institution that has the individualism as its scholar culture. The theoretical referential of the study integrates the areas of the knowledge of the professor, searching to understand how this is developed and clarified; of the school culture in the perspective to observe its interference in the professional development of the formers of teachers, and the didactic aspects of the area of knowledge of Differential and Integral Calculus that constitutes a source to know of the formers of Mathematics teachers. The research methodology follows a qualitative boarding, of the type case study . A collective work group was constituted, formed for seven formers of teachers, that teach Differential and Integral Calculus, in one determined institution of superior education. The main instruments of data collection had been the document comment, interviews and analysis and had happened during the period between April,2004 until August,2006. We define categories from our theoretical referential, that made us possible to organize and to understand the collected data. From this study it is possible to agree with Hargreaves (1998) that the contribution is one of the most promising paradigms for the professional development of the formers of teachers, therefore it makes possible to elucidate the doubts related to the learning practical , to argue concepts that had not been argued during the formal formation and recreate some teach-and-learn conceptions. Also we have analyzed the difficulties so that a collective work group pass to a collaborative form and we have concluded that the main ones are: the lack of the experience in organizing the guideline that will guide the works; the excess of unarticulated personal impressions with theories that lead to generating quarrels; a false expectation to find magical solutions; little knowledge on the possibility of the reflection on the action as a strategy of professional development; the lack of the habit to search the practical itself. Finally, we can affirm that in the group that we have investigated there are different possibilities of the transition from a collective work to a collaborative one; among them we focus: the objectives in common of the formers, the necessity of the exchange of experience and the quarrel of specific didactic knowledge of the area of Differential and Integral Calculus, the search of support to face the necessary curricular changes, the climate of camaraderie and confidence constructed throughout the meetings, the search of specific knowledge of the Differential and Integral Calculus